Small-size platinum-based ordered alloy catalyst as well as preparation method and application thereof
By using aromatic amine ligand and mesoporous carbon at high temperature, the aggregation and maturation growth of platinum-based alloy nanoparticles was suppressed, and the problem of size increase of Pt-based catalysts in high temperature environments was solved, and a small size was prepared Platinum-based ordered alloy catalysts have improved catalytic activity and service life.
Patent Information
- Application Number
- CN202310729697.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-19
- Publication Date
- 2024-12-20
AI Technical Summary
Existing Pt-based catalysts are prone to agglomeration and maturation growth in high temperature environments, resulting in an increase in particle size and affecting catalytic activity. The low earth abundance and high cost of precious metal Pt limit the widespread application of fuel cells.
The co-limiting domain action of aromatic amine ligand and mesoporous carbon is adopted to form a small-sized platinum-based ordered alloy catalyst through high-temperature heat treatment, which inhibits the agglomeration and maturation growth of platinum-based alloy nanoparticles, and improves the catalytic capacity and service life of the catalyst.
A small-size platinum-based ordered alloy catalyst with a particle size of 1.5-4.0 nm was successfully prepared, showing excellent structural stability and catalytic activity, reducing the cost of the catalyst and improving its service life.
Smart Images

Figure CN119170807A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of micro-nano material preparation, and more specifically to a small-sized platinum-based ordered alloy catalyst and a preparation method and application thereof. Background Art
[0002] Hydrogen energy is known as the ultimate energy source of the 21st century due to its high calorific value and pollution-free products. Proton exchange membrane fuel cells are currently the most efficient means of converting the chemical energy of hydrogen into electrical energy. Among them, Pt / C catalysts are currently the most widely used commercial fuel cell catalysts due to their high catalytic activity in oxygen reduction reactions. However, the low earth abundance and high cost of the precious metal Pt severely limit the large-scale application of Pt / C catalysts in fuel cells, and also affect the cost of proton exchange membrane fuel cells. Therefore, the development of highly active, low-cost oxygen reduction electrocatalysts is currently the core issue affecting the development of proton exchange membrane fuel cells.
[0003] At present, alloying Pt with other transition metals can greatly improve the mass activity of Pt-based catalysts in oxygen reduction reactions, thereby reducing the use of Pt metal and reducing the cost of catalysts. Among them, Pt-based ordered phase alloys (also known as intermetallic compounds) have a regular atomic arrangement, which can further prevent the dissolution of transition metals while having excellent catalytic performance, thus combining performance and stability. However, ordered phase alloys usually require high-temperature heat treatment above 700°C to obtain, and alloy particles are prone to agglomeration and ripening growth in high-temperature environments, which will cause the alloy particles to become larger in size and seriously affect the catalytic activity of the catalyst. In order to solve this problem, some studies have reported that the agglomeration and ripening growth of alloy particles are inhibited by coating oxides such as SiO2 and MgO, but these methods make the preparation of catalysts more complicated and introduce factors that affect the performance of catalysts. Therefore, the development of a synthesis method for small-sized Pt-based ordered alloy catalysts remains a very challenging research topic. Summary of the invention
[0004] Based on the above defects, the first object of the present invention is to provide a method for preparing a small-sized platinum-based ordered alloy catalyst. The preparation method mainly utilizes the co-confinement effect of aromatic amine ligands and mesoporous carbon. The preparation method is easy to operate, inhibits the agglomeration and ripening growth of platinum-based alloy nanoparticles during the phase transition process, forms a highly ordered small-sized platinum-based alloy catalyst, and improves the catalytic ability and service life of the catalyst.
[0005] The second object of the present invention is to provide a small-sized platinum-based ordered alloy catalyst prepared by the preparation method as described above. The particle size of the platinum-based ordered alloy catalyst is small, 1.5-4.0nm, and the ordered phase PtM alloy is uniformly dispersed in the mesoporous carbon material, showing good structural stability and catalytic activity.
[0006] The third object of the present invention is to provide a use of the platinum-based ordered alloy catalyst as described above in an electrocatalytic oxygen reduction reaction.
[0007] In order to achieve the above first object, the present invention adopts the following technical scheme:
[0008] The present invention discloses a method for preparing a small-sized platinum-based ordered alloy catalyst, comprising the following steps:
[0009] The mesoporous carbon material, Pt salt and non-Pt transition metal salt are dispersed in an organic solvent, and a suspension A is obtained after ultrasonication;
[0010] Dispersing aromatic amine in an organic solvent to obtain solution B;
[0011] Solution B is added to suspension A, and solution C is obtained after stirring, and the solvent is removed to obtain a precursor;
[0012] The precursor is subjected to high-temperature heat treatment in a mixed atmosphere of hydrogen and argon to obtain the product.
[0013] In the present invention, based on the problem of easy agglomeration of platinum-based alloys and large particle size caused by particle growth in the prior art, the present invention discloses a preparation method for preparing highly ordered small-sized platinum-based alloy catalysts. In the preparation method, in order to control the agglomeration and ripening growth of platinum-based alloy nanoparticles during high-temperature phase transition, the present invention provides a method for co-confining an organic ligand and mesoporous carbon. The preparation method uses aromatic amines as ligands to coordinate with non-Pt transition metals. After the ligands are carbonized, the migration of non-Pt transition metals is restricted, thereby facilitating the formation of small-sized particles. In addition, mesoporous carbon materials are selected as carriers, and the suitable pore size can accommodate appropriate metal precursors, and further inhibit the ripening growth of particles. The co-confining effect of ligands and mesoporous carbon provides an efficient method for the preparation of small-sized platinum-based ordered alloy catalysts. The preparation method is simple to operate, inhibits the agglomeration and ripening growth of platinum-based alloy nanoparticles during high-temperature phase transition, forms highly ordered small-sized platinum-based ordered alloy catalysts, and improves the catalytic ability and service life of the catalyst.
[0014] Furthermore, the aromatic amine includes, but is not limited to, one or more of o-phenylenediamine, 2,2-bipyridylamine, m-phenylenediamine, p-phenylenediamine, dimethylpyridylamine, 2-aminopyridine and 2,6-diaminopyridine, preferably 2,2-bipyridylamine.
[0015] Furthermore, the molar ratio of the aromatic amine to the Pt salt is 2-7:1; preferably, the molar ratio of the aromatic amine to the Pt salt is 3.3-5:1, preferably 4:1.
[0016] Furthermore, before adding solution B to suspension A, suspension A needs to be stirred continuously for 4-7 hours to fully mix the materials in suspension A. After solution B is added, it needs to be stirred for 15-20 hours to obtain solution C.
[0017] Furthermore, the metal in the non-Pt transition metal salt includes one of Co, Fe, Ni, Zn, Cu and Mn.
[0018] Further, the non-Pt transition metal salt includes but is not limited to one or more of non-Pt transition metal chlorides, non-Pt transition metal nitrates, non-Pt transition metal oxalates, non-Pt transition metal sulfates, and non-Pt transition metal acetylacetonates; preferably, non-Pt transition metal nitrates; more preferably, the non-Pt transition metal nitrate is selected from one of Co(NO3)2·6H2O, Fe(NO3)3·9H2O, Mn(NO3)2·4H2O, Cu(NO3)2·3H2O, Ni(NO3)2·6H2O and Zn(NO3)2·6H2O.
[0019] Furthermore, the molar ratio of the Pt salt to the non-Pt transition metal salt is 0.5-3.5:1; preferably, the molar ratio of the Pt salt to the non-Pt transition metal salt is 0.8-1.2:1; more preferably, the molar ratio of the Pt salt to the non-Pt transition metal salt is 1:1.
[0020] Furthermore, the Pt salt includes but is not limited to one or more of platinum acetylacetonate, chloroplatinic acid, and platinum chloride salt; preferably platinum acetylacetonate.
[0021] Furthermore, the mesoporous carbon material includes but is not limited to one or more of Ketjenblack Ecp-600JD carbon black, Vulcan XC-72 carbon black, mesoporous carbon spheres and acetylene black; preferably mesoporous carbon spheres, wherein the mesoporous carbon material can be purchased or synthesized by itself; more than 80% of the pores in the mesoporous carbon spheres are concentrated between 3-10 nm, and commercially available mesoporous carbon spheres that meet the pore distribution requirements can be selected, or they can be synthesized by themselves. The synthesis method adopts a general hard template method, which can be prepared by referring to the literature (Adv. Mater. 2020, 32, 1901349).
[0022] Furthermore, in the suspension A, the mass concentration of the mesoporous carbon material is 4-8 mg·mL -1 , preferably 5 mg·mL -1 .
[0023] Furthermore, the suspension A is obtained by ultrasonication for 0.2-1 h, preferably 0.5 h.
[0024] Furthermore, the mass ratio of the mesoporous carbon material to the Pt salt is 0.5-5:1, preferably 1.5:1.
[0025] Furthermore, the precursor is heat treated in a mixed atmosphere of hydrogen and argon, wherein hydrogen is a reducing gas and the mixed atmosphere is argon containing 10% hydrogen. Exemplarily, the gas flow rate of the mixed gas is 120 ml / min.
[0026] Furthermore, the temperature of the high temperature heat treatment is 600-1000°C and the temperature is kept for 2-4 hours, so that the particle size of the ordered phase PtM alloy is 1.5-4.0nm; preferably, the temperature of the high temperature heat treatment is 900°C and the temperature is kept for 3 hours.
[0027] Furthermore, the organic solvent includes, but is not limited to, one or more of ethanol, acetone, methanol and dichloromethane; preferably acetone.
[0028] Furthermore, the method for removing the solvent may be oven drying or rotary evaporation drying to achieve the purpose of removing the solvent.
[0029] In order to achieve the above second purpose, the present invention adopts the following technical solutions:
[0030] The present invention discloses a small-sized platinum-based ordered alloy catalyst, which is prepared by the preparation method described above;
[0031] The platinum-based ordered alloy catalyst has a small-sized ordered phase PtM alloy as an active component and a mesoporous carbon material as a carrier;
[0032] Wherein, the M metal is selected from one of Co, Fe, Ni, Zn, Cu and Mn; illustratively, the ordered phase PtM alloy can be an ordered phase PtCo alloy, an ordered phase PtFe alloy, an ordered phase PtMn alloy, an ordered phase PtCu alloy, etc., and the obtained platinum-based ordered alloy catalysts are named L10-PtCo, L10-PtFe, L10-PtMn, and L11-PtCu, respectively.
[0033] Compared with the disordered Pt-based alloy obtained under low-temperature heat treatment conditions, in the platinum-based ordered alloy catalyst provided by the present invention, since the Pt atoms and the M metal atoms occupy specific unit cell positions, there is a strong dd orbital interaction between the atoms in the c-axis direction, showing excellent structural stability.
[0034] Furthermore, the particle size of the ordered phase PtM alloy is 1.5-4.0 nm.
[0035] Furthermore, in the ordered phase PtM alloy, the atomic ratio of Pt and M metal is 1:0.8-1.2; the Pt and M are arranged in an ordered face-centered tetragonal manner, and this ordered structure is conducive to maintaining stability in electrocatalytic tests.
[0036] Furthermore, the loading amount of Pt in the platinum-based ordered alloy catalyst is 10-50wt%.
[0037] In order to achieve the third object, the present invention adopts the following technical solutions:
[0038] The present invention discloses an application of the above-mentioned platinum-based ordered alloy catalyst in an electrocatalytic oxygen reduction reaction.
[0039] The beneficial effects of the present invention are as follows:
[0040] The present invention discloses a small-sized platinum-based ordered alloy catalyst and a preparation method thereof, which has the following advantages over the prior art:
[0041] In the preparation method provided by the present invention, aromatic amine is selected as a ligand to coordinate with a non-Pt transition metal, and the migration of the non-Pt transition metal is restricted after the ligand is carbonized, thereby facilitating the formation of small-sized Pt-based nanoparticles, and a mesoporous carbon material is selected as a carrier, and the suitable pore size is conducive to loading an appropriate amount of metal precursor, and further restricting the growth of nanoparticles. The preparation method is simple to operate, has universality, inhibits the agglomeration and ripening growth of platinum-based alloy nanoparticles during the phase transition process, forms a highly ordered small-sized platinum-based alloy catalyst, and improves the catalytic ability and service life of the catalyst.
[0042] The present invention also provides a small-sized platinum-based ordered alloy catalyst, which uses an ordered phase PtM (M is Co, Fe, Ni, Zn, Cu or Mn) alloy as an active component and a mesoporous carbon material as a carrier. It is a new type of platinum-based ordered alloy catalyst. The particle size of the ordered phase PtM alloy is 1.5-4.0 nm, the particle size is relatively small, and the Pt atoms and non-Pt transition metal atoms occupy specific unit cell positions. There is a strong dd orbital interaction between the atoms in the c-axis direction, showing excellent structural stability. At the same time, this interaction gives it suitable oxygen and intermediate product adsorption energy and excellent ability to resist transition metal dissolution. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] The specific implementation modes of the present invention will be further described in detail below in conjunction with the accompanying drawings.
[0044] Figure 1Powder diffraction (XRD) spectra of L10-PtCo, L10-PtFe, L10-PtMn, and L11-PtCu ordered alloy catalysts obtained in Examples 1-4 of the present invention are shown.
[0045] Figure 2 Transmission electron microscope (TEM) images of L10-PtCo, L10-PtFe, L10-PtMn, and L11-PtCu ordered alloy catalysts obtained in Examples 1-4 of the present invention are shown.
[0046] Figure 3 Spherical aberration-corrected transmission electron microscopy (HAADF-STEM) images of the L10-PtCo, L10-PtFe, L10-PtMn, and L11-PtCu ordered alloy catalysts obtained in Examples 1-4 of the present invention are shown.
[0047] Figure 4 Atomic-resolution spherical aberration-corrected transmission electron microscopy (AC-HAADF-STEM) images of the L10-PtCo, L10-PtFe, L10-PtMn, and L11-PtCu ordered alloy catalysts obtained in Examples 1-4 of the present invention are shown.
[0048] Figure 5 The EDS-mapping diagram of the L10-PtCo ordered alloy catalyst obtained in Example 1 of the present invention is shown.
[0049] Figure 6 The TEM image of the L10-PtCo ordered alloy catalyst obtained in Example 5 of the present invention is shown.
[0050] Figure 7 The XRD pattern of the L10-PtCo ordered alloy catalyst obtained in Example 5 of the present invention is shown.
[0051] Figure 8 The XRD patterns of the L10-PtCo ordered alloy catalysts obtained in Comparative Example 1 and Example 6 of the present invention are shown.
[0052] Fig. 9 The XRD pattern of the L10-PtCo ordered alloy catalyst obtained in Comparative Example 2 of the present invention is shown.
[0053] Fig.10 The XRD pattern of the L10-PtCo ordered alloy catalyst obtained in Comparative Example 3 of the present invention is shown.
[0054] Fig.11 The XRD pattern of the disordered PtCo alloy catalyst obtained in Comparative Example 4 of the present invention is shown.
[0055] Fig.12The XRD pattern of the L10-PtCo ordered alloy catalyst obtained in Comparative Example 5 of the present invention is shown.
[0056] Fig.13 The XRD pattern of the L10-PtCo ordered alloy catalyst obtained in Comparative Example 6 of the present invention is shown.
[0057] Fig.14 It shows that the L10-PtCo ordered alloy catalyst in Example 7 of the present invention is -1 Electrocatalytic oxygen reduction activity diagram in HClO4 solution.
[0058] Fig.15 It shows that the L10-PtCo ordered alloy catalyst in Example 8 of the present invention is -1 Stability diagram of electrocatalytic oxygen reduction in HClO4 solution. DETAILED DESCRIPTION
[0059] In order to more clearly illustrate the present invention, the present invention is further described below in conjunction with preferred embodiments and accompanying drawings. Similar components in the accompanying drawings are represented by the same reference numerals. It should be understood by those skilled in the art that the content specifically described below is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.
[0060] The mesoporous carbon spheres used in the present invention are prepared according to reference (Adv. Mater. 2020, 32, 1901349).
[0061] Example 1
[0062] A method for preparing an ordered phase L10-PtCo alloy supported by a mesoporous carbon material comprises the following steps:
[0063] 1) Weigh 45 mg of mesoporous carbon spheres, 30 mg of platinum acetylacetonate and 22.2 mg of Co(NO3)2·6H2O into 13.85 mL of acetone and sonicate for 30 min to obtain a uniform suspension A;
[0064] 2) Disperse 52.23 mg of 2,2-dipyridinamine in 2.6 mL of acetone to obtain solution B;
[0065] 3) After the suspension A was stirred evenly at room temperature for 5 hours, the solution B was added to the suspension A, and the stirring was continued for 17 hours to obtain the solution C, and then the precursor solid sample was collected by drying;
[0066] 4) In a 10% H2 / Ar atmosphere, the precursor solid sample was subjected to high temperature heat treatment in a tube furnace, heated to 900°C, calcined for 3 hours, and then naturally cooled to room temperature to obtain a platinum-based ordered alloy catalyst, denoted as L10-PtCo, wherein the mixed gas flow rate was 120 ml / min.
[0067] The powder X-ray diffraction of L10-PtCo prepared in this example is shown in Figure 1 .
[0068] The transmission electron microscopy of L10-PtCo prepared in this example shows Figure 2 .
[0069] The spherical aberration corrected transmission electron microscopy image of L10-PtCo prepared in this example is shown in Figure 3 .
[0070] The atomic resolution spherical aberration corrected transmission electron microscopy of L10-PtCo prepared in this example shows Figure 4 .
[0071] The energy spectrometer scan of L10-PtCo prepared in this example is shown in Figure 5 .
[0072] Depend on Figure 1 It can be seen that the XRD pattern of the synthesized L10-PtCo shows characteristic peaks of the ordered phase, indicating that the atoms are arranged in an orderly manner. Figure 2 and Figure 3 It can be seen that the synthesized ordered phase PtCo alloy is uniformly dispersed on the mesoporous carbon support, and its average diameter is 2.7nm. Figure 4 It can be seen that the Pt atoms and Co atoms are arranged in order in the particles. Figure 5 It can be seen that the N derived from the carbonization of the aromatic amine ligand is uniformly dispersed in the carbon support.
[0073] Example 2
[0074] The preparation process of Example 1 was repeated, with the only difference being that 22.2 mg Co(NO3)2·6H2O was replaced by 30.81 mg Fe(NO3)3·9H2O, to obtain a platinum-based ordered alloy catalyst, which was designated as L10-PtFe.
[0075] Example 3
[0076] The preparation process of Example 1 was repeated, with the only difference being that 22.2 mg Co(NO3)2·6H2O was replaced by 18.42 mg Cu(NO3)2·3H2O and the heat treatment temperature was changed to 800°C to obtain a platinum-based ordered alloy catalyst, which was recorded as L11-PtCu.
[0077] Example 4
[0078] The preparation process of Example 1 was repeated, with the only difference being that 22.2 mg Co(NO3)2·6H2O was replaced by 19.14 mg Mn(NO3)2·4H2O and the heat treatment temperature was changed to 800°C to obtain a platinum-based ordered alloy catalyst, recorded as L10-PtMn.
[0079] The powder X-ray diffraction patterns of L10-PtFe, L11-PtCu and L10-PtMn prepared in Example 2-4 are shown in Table 1. Figure 1 .
[0080] The transmission electron micrographs of L10-PtFe, L11-PtCu, and L10-PtMn prepared in Example 2-4 are shown in FIG. Figure 2 .
[0081] The spherical aberration corrected transmission electron microscopy images of L10-PtFe, L11-PtCu, and L10-PtMn prepared in Example 2-4 are shown in Figure 3 .
[0082] Atomic resolution spherical aberration corrected transmission electron microscopy of L10-PtFe, L11-PtCu, and L10-PtMn prepared in Example 2-4 shows Figure 4 .
[0083] Depend on Figure 2-Figure 3 It can be seen that the synthesized ordered phase PtFe alloy, PtCu alloy and PtMn alloy are uniformly dispersed on the mesoporous carbon support, and their average diameters are 2.8nm, 2.5nm and 1.8nm, respectively.
[0084] Example 5
[0085] The preparation process of Example 1 was repeated, with the only difference being that the mesoporous carbon spheres used were replaced with Ketjenblack Ecp-600JD carbon black. Figure 6 It is shown that uniform ordered phase PtCo alloy particles can be formed on Ketjenblack Ecp-600JD carbon black. Figure 7 The XRD curve shows that a small-sized ordered phase PtCo alloy can be formed on Ketjenblack Ecp-600JD carbon black, and the average particle size is 2.83nm.
[0086] Example 6
[0087] The preparation process of Example 1 was repeated, with the only difference being that the heat treatment temperature was changed to 1000° C. and the other conditions remained unchanged, to prepare the catalyst. Figure 8 The XRD pattern of the obtained catalyst is shown, indicating that an ordered phase PtCo alloy can still be formed at 1000°C.
[0088] Comparative Example 1
[0089] The preparation process of Example 1 was repeated, except that the heat treatment temperature was changed to 800° C. and other conditions remained unchanged, to prepare a catalyst. Figure 8 The XRD pattern of the obtained catalyst is shown. The appearance of the characteristic peak of the ordered phase indicates that the transition from the disordered phase to the ordered phase can still occur at this temperature, but the ordered peak is relatively weak.
[0090] Comparative Example 2
[0091] The preparation process of Example 1 was repeated, except that the heat treatment time was reduced to 2 hours. Fig. 9 The XRD curve of the sample also shows the characteristic peak of the ordered phase, indicating that the ordered phase of PtCo alloy can also be formed by reducing the heat treatment time at 900°C, but the degree of order is relatively low.
[0092] Comparative Example 3
[0093] The preparation process of Example 1 was repeated, except that the heat treatment time was extended to 4 hours. Fig.10 The XRD curve of the sample also showed characteristic peaks of the ordered phase, indicating that an ordered phase of PtCo alloy can also be formed by extending the heat treatment time at 900°C, but the main peak of XRD becomes sharper and the particles become larger, with an average particle size of 4.36nm.
[0094] Comparative Example 4
[0095] The preparation process of Example 1 was repeated, except that the heat treatment temperature was changed to 500°C. Fig.11 From the XRD pattern of the prepared catalyst, it can be seen that no transition from the disordered phase to the ordered phase occurs under the condition of 500°C, and the prepared catalyst is still a disordered PtCo alloy catalyst.
[0096] Comparative Example 5
[0097] The preparation process of Example 1 was repeated, except that the mesoporous carbon spheres were replaced with BLACK 2000 Carbon Black. Fig.12 The XRD curve is shown in BLACK An ordered phase PtCo alloy can be formed on 2000 carbon black, but the main peak of XRD is very sharp and its average particle size is about 5.37nm.
[0098] BLACK The characteristic of 2000 carbon black is that most of its pores are micropores, which will restrict the complexes of Co and aromatic amine from entering the pores, making it impossible to utilize the confinement effect of the pores. Its inability to synthesize small-sized ordered alloys also proves the supporting and confinement effects of mesopores in this system.
[0099] Comparative Example 6
[0100] The preparation process of Example 1 was repeated, except that no organic ligand was added. Fig.13 The XRD curve shows that an ordered phase PtCo alloy is formed, but the main peak of XRD is very sharp, and its average particle size is about 7.98nm.
[0101] The particles generated without adding ligands are very large, which is very different from those with adding ligands, proving the confining effect of ligands in this system.
[0102] Example 7
[0103] An application of an ordered L10-PtCo alloy supported by a mesoporous carbon material in electrocatalytic oxygen reduction, the application comprising the following steps:
[0104] 1) 4 mg of the sample obtained in Example 1 was dissolved in 1 mL of a mixed solution of isopropanol, distilled water and Nafion solution (wherein the volumes of isopropanol, distilled water and Nafion were 495 μL, 495 μL and 10 μL, respectively) and ultrasonicated for 1 hour to form a uniform slurry.
[0105] 2) Take 5 μL of the above uniform slurry and drop it onto the rotating disk electrode. Dry it at room temperature to form a uniform film. Then, -1 The test was carried out in a solution of HClO4 with a test voltage range of 0-1.1V (relative to the standard hydrogen electrode). The test results are as follows Fig.14 The synthesized sample showed excellent electrocatalytic performance for oxygen reduction to water, with a half-wave potential of 0.957 V. The mass activity and specific activity of the sample were 4.24 A mg Pt -1 and 4.31 mA cm Pt -2 .
[0106] According to the same application steps and conditions as Example 7, the mass activity and specific activity of the samples prepared in Examples 2-6 and Comparative Examples 1-6 were tested in sequence. The test results are shown in Table 1.
[0107] Table 1 Electrocatalytic test data of samples prepared in Examples 2-6 and Comparative Examples 1-6
[0108] sample <![CDATA[Mass activity (A mg Pt -1 )]]> <![CDATA[Specific activity (mA cm Pt -2 )]]> Example 2 3.25 3.53 Example 3 1.09 1.31 Example 4 0.74 0.61 Example 5 2.41 2.25 Example 6 2.78 3.08 Comparative Example 1 2.31 2.39 Comparative Example 2 3.24 3.48 Comparative Example 3 2.58 2.94 Comparative Example 4 1.54 1.89 Comparative Example 5 1.12 1.68 Comparative Example 6 0.59 1.12
[0109] Example 8
[0110] An application of a mesoporous carbon material-supported L10-PtCo ordered phase alloy in electrocatalytic oxygen reduction, the application comprising the following steps:
[0111] 1) 4 mg of the sample obtained in Example 1 was dissolved in 1 mL of a mixed solution of isopropanol, distilled water and Nafion solution (wherein the volumes of isopropanol, distilled water and Nafion were 495 μL, 495 μL and 10 μL, respectively) and ultrasonicated for 1 hour to form a uniform slurry. Then 5 μL of the uniform slurry was dropped onto a rotating disk electrode and dried at room temperature to form a uniform film. -1 The initial LSV curves were collected in HClO4 solution.
[0112] 2) Cyclic voltammetry was performed in the voltage range of 0.6-1 V relative to the standard hydrogen electrode, and another LSV curve was collected after 10,000 cycles to evaluate the stability of the catalyst. Fig.15 After 10,000 cycles of cyclic voltammetry scanning, the LSV curves can basically remain overlapping, indicating that the catalyst has excellent stability.
[0113] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.
Claims
1. A method for preparing a small-sized platinum-based ordered alloy catalyst, characterized in that: The steps include: The mesoporous carbon material, Pt salt and non-Pt transition metal salt are dispersed in an organic solvent, and a suspension A is obtained after ultrasonication; Dispersing aromatic amine in an organic solvent to obtain solution B; Solution B is added to suspension A, and solution C is obtained after stirring, and the solvent is removed to obtain a precursor; The precursor is subjected to high-temperature heat treatment in a mixed atmosphere of hydrogen and argon to obtain the product.
2. The preparation method according to claim 1, characterized in that: The aromatic amine includes one or more of o-phenylenediamine, 2,2-dipyridylamine, m-phenylenediamine, p-phenylenediamine, dimethylpyridylamine, 2-aminopyridine and 2,6-diaminopyridine; Preferably, the molar ratio of the aromatic amine to the Pt salt is 2-7:
1.
3. The preparation method according to claim 1, characterized in that: The non-Pt transition metal salt includes one or more of a non-Pt transition metal chloride, a non-Pt transition metal nitrate, a non-Pt transition metal oxalate, a non-Pt transition metal sulfate, and a non-Pt transition metal acetylacetonate; Preferably, the metal in the non-Pt transition metal salt includes one of Co, Fe, Ni, Zn, Cu and Mn; Preferably, the molar ratio of the Pt salt to the non-Pt transition metal salt is 0.5-3.5:
1.
4. The preparation method according to claim 1, characterized in that: The Pt salt includes one or more of platinum acetylacetonate, chloroplatinic acid and platinum chloride salt.
5. The preparation method according to claim 1, characterized in that: The mesoporous carbon material includes one or more of Ketjenblack Ecp-600JD carbon black, Vulcan XC-72 carbon black, mesoporous carbon spheres and acetylene black; Preferably, the mass ratio of the mesoporous carbon material to the Pt salt is 0.5-5:
1.
6. The preparation method according to claim 1, characterized in that: The high temperature heat treatment is carried out at a temperature of 600-1000° C. and maintained for 2-4 hours to make the particle size of the ordered phase PtM alloy be 1.5-4.0 nm.
7. A small-sized platinum-based ordered alloy catalyst, characterized in that: Prepared by the preparation method according to any one of claims 1 to 6; The platinum-based ordered alloy catalyst has a small-sized ordered phase PtM alloy as an active component and a mesoporous carbon material as a carrier; Wherein, the M metal is selected from one of Co, Fe, Ni, Zn, Cu and Mn.
8. The platinum-based ordered alloy catalyst according to claim 7, characterized in that: The particle size of the ordered phase PtM alloy is 1.5-4.0 nm; Preferably, in the ordered phase PtM alloy, the atomic ratio of Pt to M is 1:0.8-1.2; The Pt and M metals present an ordered face-centered tetragonal arrangement.
9. The platinum-based ordered alloy catalyst according to claim 7, characterized in that: The loading amount of Pt in the platinum-based ordered alloy catalyst is 10-50 wt %.
10. Use of the platinum-based ordered alloy catalyst according to any one of claims 7 to 9 in an electrocatalytic oxygen reduction reaction.
